2009
DOI: 10.1093/carcin/bgp208
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of microRNA expression in vinyl carbamate-induced mouse lung tumors and modulation by the chemopreventive agent indole-3-carbinol

Abstract: MicroRNAs (miRNAs) are small, non-protein-coding RNAs that can function as tumor suppressors or oncogenes. Deregulation of miRNA expression has been reported in lung cancer. However, modulation of miRNA expression by chemopreventive agents remains to be defined. In the present study, we examined if the chemopreventive agent indole-3-carbinol (I3C) reversed vinyl carbamate (VC)-induced deregulation of miRNA levels in lung tissues of female A/J mice. Lung tissues were obtained from a previous chemoprevention stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 32 publications
6
97
0
1
Order By: Relevance
“…The analysis of miRNAs by microarray method revealed a significant upregulation of miR21, miR31, miR130a and miR146b in lung tumors of mice. While in mice treated with vinyl carbamate and given I3C diet the expression level of these miRNAs were significantly reduced relative to the expression level of mice were treated with vinyl carbamate alone (17). Our study showed parallel results regarding the expression tendency of miR21and miR146a.…”
supporting
confidence: 72%
“…The analysis of miRNAs by microarray method revealed a significant upregulation of miR21, miR31, miR130a and miR146b in lung tumors of mice. While in mice treated with vinyl carbamate and given I3C diet the expression level of these miRNAs were significantly reduced relative to the expression level of mice were treated with vinyl carbamate alone (17). Our study showed parallel results regarding the expression tendency of miR21and miR146a.…”
supporting
confidence: 72%
“…For example, up-regulation of miR146b could inhibit the metastasis of breast cancer (Hurst et al 2009), and glioma (Xia et al 2009). A number of other studies observed over-expression of miR-146b in cancer (Melkamu et al 2010;Chen et al 2008;Fulci et al 2009). The stimulatory effect of TGF-b on differentiation of intestinal epithelial cells is closely associated with its tumor suppressing effects; therefore, it is of significance to examine whether and how miR-146b is involved in this important biological process.…”
Section: Discussionmentioning
confidence: 93%
“…It is well known that small non-coding regulatory RNAs -microRNAs (miRs) are found to be dysregulated in almost all types of cancers and play important roles in cancer development and progression (13)(14)(15)(16)(17). Recent studies have demonstrated that miRs can be regulated by natural agents such as curcumin and Res resulting in suppression of tumor growth, drug resistance and metastasis (18)(19)(20)(21). Our previous studies have confirmed that specific miRs, including miR-21, miR19 and miR-30a-5p are upregulated in GBMs with significant oncogenic activity and their major targeted genes involved in gliomagenesis (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%